Review of A Manichaean Prayer and Confession Book - Benkato, Adam (JAOS, 2024)
A Manichaean Prayer and Confession Book. Edited and translated by Nicholas Sims-Williams, with introduction by John Sheldon and codicology by Zsuzsanna Gulácsi. Corpus Fontium Manichaeorum, Series Iranica, vol. 1. Turnhout: Brepols, 2022. Pp. xxvi + 195. €100.